2022
DOI: 10.3390/jof8050475
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Rot of Pomegranate Fruit in Southern Italy: Characterization of the Main Pathogens

Abstract: Pomegranate (Punica granatum L.) is an emerging crop in Italy and particularly in southern regions, such as Apulia, Basilicata, and Sicily, due to favorable climatic conditions. The crop is affected by several pathogenic fungi, primarily in the field, but also during postharvest phases. The most important postharvest fungal diseases in pomegranate are gray and blue molds, black heart and black spot, anthracnose, dry rot, and various soft rots. The limited number of fungicides allowed for treatment in the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 79 publications
0
41
0
Order By: Relevance
“…Moreover, a number of species of Alternaria , including A. solani , have been reported to infect pomegranate [ 22 , 28 , 60 ]; however, many of these species were not represented among the isolates characterized in the current study. Alternaria species, due to their high adaptivity to different environmental conditions, can infect pomegranate fruits in both pre- and post-harvest stages [ 61 ]; they produce toxins which are important for their virulence and may contaminate fruits and the products processed downstream [ 22 ]. Moreover, some species, such as A. gaisen , are quarantine pathogens imposing export restrictions, and therefore accurate identification of Alternaria species also has toxicological and phytosanitary implications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a number of species of Alternaria , including A. solani , have been reported to infect pomegranate [ 22 , 28 , 60 ]; however, many of these species were not represented among the isolates characterized in the current study. Alternaria species, due to their high adaptivity to different environmental conditions, can infect pomegranate fruits in both pre- and post-harvest stages [ 61 ]; they produce toxins which are important for their virulence and may contaminate fruits and the products processed downstream [ 22 ]. Moreover, some species, such as A. gaisen , are quarantine pathogens imposing export restrictions, and therefore accurate identification of Alternaria species also has toxicological and phytosanitary implications.…”
Section: Resultsmentioning
confidence: 99%
“…Hyphae were flocculent or villous and denser ( Figure 2 E), the conidia were elongated oval and slightly pointed at both ends ( Figure 3 E), which was consistent with the morphology of F. oxysporum isolated from sesame plants. Previous study revealed that Fusarium species is attributed to “latent infected pathogen” [ 38 ], the infection of Fusarium usually occur in the field (growth stage of plants) during the blooming or heading of plants. The spores adhere to the surface of the leaf, then transported into the calyx, finally colonize on the root of plants, and remain in a latent status until there are favorable environmental conditions (such as high temperature and humidity) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For fungal isolation, the diseased tissues were cut into several small segments and placed on potato dextrose agar (PDA, Difcohai) at 25 °C in darkness for 3 to 5 days. To obtain pure cultures, hyphal tips from developed colonies were transferred to fresh PDA plates three times [ 10 ]. The isolates were inoculated to PDA test tube slants and stored at 4 °C [ 11 ].…”
Section: Methodsmentioning
confidence: 99%